The Construction and Response of Brand Competitiveness Evaluation Index System of Fresh Agricultural Products Supermarket under the Background of Big Data - Wang, Lei; Liu, Jing; Sun, Tongtong (Economics & Management Review, 2024)
Under the background of big data, the competition becomes a kind of brand competition, and the strong brand can bring competitive advantage. With the rapid development of the fresh agricultural supermarket, the competition between which is increasingly fierce. Therefore the research of the system about the brand competitiveness’ evaluation index has important significance for the development of the fresh agricultural supermarket. The conclusions is shown as follows: the elements that affect the brand competitiveness of the fresh agricultural supermarket are employees capacity, marketing ability, profitability, brand image and development potential, the profit ability and brand image are the most important. The paper established the evaluation index of the fresh agricultural supermarket’s brand competitiveness, established the weight of each index, by using the analytic hierarchy process (AHP), and established the system of the evaluation index. Finally, the empirical research of the fresh Z agricultural supermarket verified the effectiveness of the system.